Realisasi Kebijakan Energi Terbarukan Uni Eropa (UE) oleh Denmark dalam Upaya Menghadapi Ancaman Pemanasan Global - Yovita Yiwananda; Henny Saptatia Drajati Nugrahani (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2021)
This research examines the realization of EU policies by Denmark in dealing with global warming through the utilization of renewable energy, with research questions, why and how the Danish mechanism in implement the policy. Denmark issued a comprehensive and integral advanced policy to respond to these threats and is considered a pioneer in the implementation of EU policies. This study explores the Danish experience using three threats of environmental security according to Barry Buzan's theory of Security. This analysis used a qualitative method with a critical approach to the implementation of Denmark in tackling the threat of global warming. The results show that the Danish’s success in realizing the EU policy is based on the eagerness to remove the stigma as a country that produces the highest greenhouse gas emissions in the world, according to the Brundtland Commission. Denmark formed three agencies under the Ministry of the Environment, which formulate a plan specifically to deal with the threat of global warming, along with the implementation of its actions. Denmark optimizes the use of renewable energy, especially wind energy as a follow-up policy instrument.